1983
DOI: 10.1083/jcb.97.5.1500
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of cells to polystyrene surfaces.

Abstract: The surface treatment of polystyrene, which is required to make polystyrene suitable for cell adhesion and spreading, was investigated. Examination of surfaces treated with sulfuric acid or various oxidizing agents using (a) x-ray photoelectron and attenuated total reflection spectroscopy and (b) measurement of surface carboxyl-, hydroxyl-, and sulfurcontaining groups by various radiochemical methods showed that sulfuric acid produces an insignificant number of sulfonic acid groups on polystyrene. This techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
234
1
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(249 citation statements)
references
References 17 publications
6
234
1
2
Order By: Relevance
“…Although we did not count adherent cells directly, it has previously been reported that about 80% of suspended BHK cells adhered to plastic tissue-culture plates in conditions similar to our own (Nath and Srere, 1977). Furthermore, we showed that in control conditions, in the absence of cytotoxin, BHK cell adhesion to plastic tissue-culture plates was maximal in 2 h. This was somewhat slower than previously observed by Nath and Srere (1977), but this may have been due to differences in several factors, including composition of serum (Knox, 1984), substrate surface (Curtis et al, 1983), and the amount of shear applied when washing unbound cells from plates.…”
Section: Discussioncontrasting
confidence: 53%
“…Although we did not count adherent cells directly, it has previously been reported that about 80% of suspended BHK cells adhered to plastic tissue-culture plates in conditions similar to our own (Nath and Srere, 1977). Furthermore, we showed that in control conditions, in the absence of cytotoxin, BHK cell adhesion to plastic tissue-culture plates was maximal in 2 h. This was somewhat slower than previously observed by Nath and Srere (1977), but this may have been due to differences in several factors, including composition of serum (Knox, 1984), substrate surface (Curtis et al, 1983), and the amount of shear applied when washing unbound cells from plates.…”
Section: Discussioncontrasting
confidence: 53%
“…The molecular composition of the membrane (sialic acid is a major contributor) and the pH and composition of the surrounding medium together give cells a negative surface charge. Curtis et al [39] have observed that, whereas surfaces bearing cations are very adhesive for cells [40], adhesion of red blood cells on anionic surfaces decreases as charge density decreases [41]. This suggests that nucleated cell adhesion could be greater on fibers than glass after topographical differences were accounted for.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Soon after, a variety of surface-synthesis strategies were explored, ranging from use of liquid-phase chemical oxidants [35,36] to application of gas-discharge treatments [37] now commonly employed in the commercial production of disposable plastic tissue cultureware [38]. Evidence mounted supporting the idea that a particular surface functional group -hydroxyl or carboxyl for example -was particularly stimulatory to cell adhesion and proliferation [39][40][41][42][43] over other functional groups. However, it has proven difficult in subsequent research to clearly separate cause-and-effect in the cell adhesion/proliferation process, especially in the ubiquitous presence of proteins, and by doing so, unambiguously separate surface chemistry from all other influences (such as surface energy/water wettability) [44].…”
Section: Cell Adhesion Theoriesmentioning
confidence: 99%